Railway Transport, its Specific Characteristics and Main Indicators - Anvarbek Ahmadjon o‘g‘li Xomidov; Sayidbek Abduvayidovich Shodmonov; Guldona Akbarjon qizi Turg‘unova (Periodica Journal, 2022)
Railway transport plays an important role in the functioning and development of the country's goods market and in satisfying the population's need for migration. It is the main link of the transport system of Uzbekistan and most countries
Keywords: Railway transport; specific characteristics; railway transport; main indicators of railway transport